Attitudes Toward Spanish and Code-Switching in Belize: Stigmatization and Innovation in the Spanish Classroom. Issue 1 (2nd January 2017) - Balam, Osmer; de Prada Pérez, Ana
ABSTRACT: Through the analysis of survey and interview data, we investigated the attitudes and perceptions of 32 multilingual teachers of Spanish in Belize, a code-switching (CS) context where Spanish is in intense contact with English and Belizean Kriol. More specifically, we examined teachers' and students' attitudes toward Spanish and CS and teachers' perceptions vis-à-vis students' attitudes toward Spanish instruction. The study revealed that whereas some teachers held negative views of Northern Belizean Spanish, they did not markedly perceive standard Spanish as "better" than the local variety of Belizean Spanish. The analysis also showed that most teachers had a positive predisposition to the use of CS as a pedagogical tool in their classrooms, a finding that suggests that ultra-normative attitudes toward Spanish varieties are not prevalent among these educators. In view of students' attitudes, teachers concurred that students had overwhelmingly negative attitudes toward standard Spanish, in line with previous findings. We argue that educational reforms and status-planning efforts are vital to destigmatize Spanish and to promote its maintenance alongside Belizean Kriol and English.